Comparison of the Influence of Vegetarian and Mediterranean Diets on the Formation of Kidney Stones - Samuła, Sebastian; Mazur, Michał; Waz, Dorota; Szarłowicz, Jakub; Goliszek, Zofia; Sobek, Karolina Łucja; Tabin-Barczak, Wiktoria; Sokołowska, Aldona; Fikas, Klaudia; Chwaliszewski, Kamil (Quality in Sport, 2025)
Introduction and Purpose: Kidney stone disease is a significant global health concern with increasing prevalence worldwide. Diet plays a critical role in both the prevention and development of this condition. The aim of this study was to compare the impact of vegetarian and Mediterranean diets on the risk of kidney stone formation, focusing on the metabolic mechanisms and nutritional composition of each diet. Materials and Methods: The review is based on a detailed analysis of peer-reviewed studies from major scientific databases such as PubMed. The selected studies focus on the mechanisms of kidney stone formation, the influence of nutritional factors on this process, and the nutritional profiles of vegetarian and Mediterranean diets. Results: The vegetarian diet, rich in citrate, magnesium, and potassium, demonstrates urine-alkalizing properties that counteract kidney stone formation. Reducing meat intake in this diet lowers the risk of hyperuricosuria and uric acid stone formation. However, the vegan version of the vegetarian diet, which excludes dairy, may increase the risk of oxalate stones due to reduced calcium intake. Conversely, the Mediterranean diet offers a more balanced approach, combining the benefits of high fruit, vegetable, olive oil, and whole grain consumption with moderate intake of dairy, fish, and poultry. The presence of polyphenols in olive oil and the anti-inflammatory properties of this diet further support metabolic health and reduce the risk of kidney stones. Conclusion: The Mediterranean diet appears more effective in reducing kidney stone risk due to its flexibility and broader range of health benefits. It combines the advantages of the vegetarian diet with additional benefits provided by dairy, healthy fats, and moderate animal protein intake. Its comprehensive preventive effects and adaptability to patient needs make it a valuable dietary model for kidney stone prevention and management.